Identifying Procedural Core Competencies for Undergraduate Emergency Medicine Education at the University of Zimbabwe College of Health Sciences - Mtombeni, Sithembile (Division of Emergency Medicine, 2019)
Introduction: Low and middle-income countries account for over 90% of worldwide morbidity and mortality associated with injuries. While insufficient resources preclude appropriate care, suboptimal clinical skills, are a universal setback. Major curricula gaps have been identified as underlying this situation. In Africa, most training efforts are targeted at postgraduate level, relegating undergraduate Emergency Medicine (EM) education to a less formal undertaking. This study set out to delineate a list of locally appropriate undergraduate EM procedural core competencies for the University of Zimbabwe College of Health Sciences (UZCHS), through a consensus building process. Methods: A three-stage modified online Delphi survey was used to gain consensus among expert medical trainers at UZCHS, between July and August 2017. Opinion was sought on a five-point Likert scale, regarding agreement with items for inclusion on the procedural core competency list. The original survey list of 105 competencies was generated from literature. The second round included suggestions from panelists. The study was ethically cleared by the University of Cape Town, UZCHS and the Medical Research council of Zimbabwe. Results: 19 expert medical teachers, representing seven clinical departments responded to the survey, with 15 completing all rounds. 79% had more than 5 years’ experience in teaching and assessment of emergency procedures. Of these, 50% had at least 10 years’ experience. The experts reached consensus (75% selecting agree or strongly agree) on 64 competencies (61%), on the first round. The second round yielded consensus on a further 33 items. Only one additional item reached consensus in the final round. A final list of 98 core procedural competencies was generated by three Delphi rounds. Qualitative comments are summarised per emerging themes. Conclusions: A locally appropriate list of undergraduate procedural core competencies, was established. This process can serve as guidance for curriculum projects in Zimbabwe and similar settings.